In situ observation of pressure modulated reversible structural changes in the graphitic domains of carbide-derived carbons. (15th April 2021) - Koppel, Miriam; Palm, Rasmus; Härmas, Riinu; Russina, Margarita; Matsubara, Nami; Månsson, Martin; Grzimek, Veronika; Paalo, Maarja; Aruväli, Jaan; Romann, Tavo; Oll, Ove; Lust, Enn
Abstract: Carbons are important in a multitude of applications, and thus, the reversible control of carbon structures is of high interest. Here we report the reversible formation of graphitic structures with three distinct interlayer distances in case of two carbide-derived carbons (CDCs) loaded under hydrogen pressure observed with in situ neutron scattering methods. The formation of these graphitic structures determined with in situ neutron diffraction is brought forth by the confinement of H2 in the porous structure when the temperature, T, is increased from T = 20 K–50 K under H2 loading from 68 mbar to 10 bar. The confinement of the desorbing H2 causes the pressure to increase inside the CDC structure and this increase of pressure is the cause for the reversible formation of graphitic domains. The confinement of H2 at T = 50 K is possible due to the presence of ultramicropores and suitable curved carbon structures. The three distinct formed graphitic domains correspond to a highly pressurized, conventional highly ordered graphitic, and disoriented graphitic domains with possible H2 /H intercalation. In situ quasi-elastic neutron scattering and gas adsorption methods are used to determine the H2 transport properties and interactions with the CDCs. Graphical abstract: Image 1 Highlights: Reversible formation of graphitic carbon structures. Formation of structures in the presence of H2 . Structure formation caused by high-pressure H2 domains after temperature increase. Curved and microporous carbons able to confine H2 pressure during heating.